APLICAÇÃO DE HIDROGEL COM DOSES DE SULFATO DE POTÁSSIONO DESENVOLVIMENTO DA CULTURA DA SOJA - Deminski, Leonardo Henrique (2022)
Faced the reduction of drinking water in the world, alternatives for efficient use of water in agriculture are being sought increasingly. Because of this, methods are studied to allerates the effects of water deficit, seeking to obtain a greater efficiency of cultivation with the available water resources, in order to ensure quality and productivity in soybean crops. Hydrogels are been used widely in agriculture due to their characteristics of soil conditioners, assisting in increasing water retention capacity. The use of hydrogel in soybean crop has the ability to increase the plant population and influence crop yield. Sulfur (S) is an essential macronutrient for plants and its low availability in soil can limit soybean yield, however, in Brazil there are few research results involving S in soybean crops. Due to these factors, the objective of the research was to evaluate the response of the use of potassium sulfate incorporated into hydrogel in soybean crops at different doses, to obtain better yields in production.This research was developed in the rural area of Cascavel - PR, in the summer harvest 2021/22. The experimental design was in Randomized Blocks in the factorial scheme 2 x 5 + 1 with 4 replications, consisting of the sources of hydrogel: ForthGel® and ForthGel®/Potassium Sulfate, and the second factor consisting of the doses: 0, 15, 20, 30, 40 and 45 kg of hydrogel per ha-1 , and the zero dose or control. Yield components and soybean yield were determined.The data were submitted to variance analysis, applying the F test at the level of 5% probability and regression, using the SISVAR Software.The data showed a statistically significant difference between the plots in relation to the total productivity, for the doses 30 and 40 kg ha-1 of hydrogel, and in the first germination count at doses 15, 30 and 45 kg ha-1 of hydrogel, while the total height, mass of 100 grains and number of plants per area did not show statistically minimal difference between the plots and doses of hydrogel and hydrogel incorporated. It was concluded that the highest soybean production was at the dose of 45 kg ha-1 of hydrogel, with 71 bags of soybean, and 15 kg ha-1 of hydrogel incorporated with potassium sulfate, with 67 bags of soybean per hectare